Hubungan perilaku sehat dan sanitasi lingkungan dengan penyakit ringworm yang ditularkan melalui kucing di Kabupaten Klaten - Anastascia Arysthia; Sitti Rahmah Umniati; Ira Parasmatri (Berita Kedokteran Masyarakat (BKM), 2017)
Hygiene and sanitation behavior of cat’s owners with dermatomycosis in KlatenPurposeThis study aimed to analyze the association of environmental hygiene and personal hygiene of cat owners with dermatomycosis in Klaten. MethodsThis research was an observational analytic epidemiological study, with a case-control design involving 60 cat owners.ResultsBivariate analysis showed that health knowledge, environmental hygiene and cat owner hygiene were associated with dermatomycosis.ConclusionLack of knowledge, healthy behavior and sanitation of cat owners increased the risk of contracting dermatomycosis. Cat owners are encouraged to behave healthy and always maintain environmental sanitation and try to prevent disease transmission.